THE FORMATION OF THE ASCETIC MOVEMENT IN MOVAROUNNAHR AND ITS SOCIO-PHILOSOPHICAL INFLUENCE - Gulnora Khudoyberganova (Modern American Journals, 2025)
This article analyzes the formation, characteristics, and impact on religious and social life of the ascetic movement in the Movarounnahr region during the 8th-9th centuries using the IMRAD system. The dominance of the Hanafi school of thought and religious tolerance during the Samanid era created a basis for the development of ascetic views. The ascetic movement became widespread among socially active strata, especially among scholars, and formed as an independent school with an internal ascetic and scholarly-theoretical nature. The activities of figures such as Abu Hafs Kabir, Abulqosim Hakim Samarkandi, and Abdullah ibn Mubarak, as well as the influence of Buddhism, Christianity, and other religious movements, were manifested in the diverse forms of asceticism. Ascetic schools emerged in centers such as Marv, Bukhara, Samarkand, and Kashkadarya, which formed the basis for later Sufi movements. The article is based on a historical-analytical method, analyzing primary sources such as Narshakhi, Maqdisi, Sam'ani, and modern research by A. Knish, A. Schimmel, K. Rakhimov, and others. The study discusses the limited information about the external manifestations and special places of worship of asceticism, emphasizing the need for further research in this area in the future.
Keywords: Asceticism, Movarounnahr, Samanids, Hanafi, Sufism, Social Movement, Religious Tolerance.